Treatment and prognosis of primary pulmonary lymphoma: A long‐term follow‐up study. (2nd November 2020) - Santopietro, Michelina; Kovalchuk, Sofia; Battistini, Roberta; Puccini, Benedetta; Annibali, Ombretta; Romano, Ilaria; Zoli, Valerio; Avvisati, Giuseppe; Bosi, Alberto; Rigacci, Luigi
Abstract: Primary pulmonary lymphoma (PPL) is a rare disease with not well‐defined optimal treatment. Outcomes and follow‐up are variable in published data. Objectives: To define the outcome and optimal treatment strategies in PPL. Methods: We reviewed the medical records of 49 patients with PPL treated in three Italian Hematological Institutions between 2002 and 2018. Results: Thirty‐eight (77.5%) cases were indolent PPL, and 11 (22.5%) cases were aggressive PPL. The majority of patients were asymptomatic at diagnosis, early stages (stages IE‐IIE), normal serum LDH, no bone marrow involvement, and low or low‐intermediate risks of IPI. Local therapy ± immunotherapy or immuno‐chemotherapy was possible in 18/49 (37%) patients. Twenty‐eight (57%) patients were treated with immuno‐chemotherapy after biopsy. Waiting and watching were reported in 3 (6%) patients. Overall, the CR and ORR were 83.7% and 95.9%. With a median follow‐up of 62.5 months (range 0.8‐199 months), the estimated 5‐ and 10‐year OS rates were 85% and 72.3% for all patients, 89.2% and 80.3% for indolent PPL, and 70.7% and 47.1% for aggressive PPL. Aggressive PPL tended to have a high risk of progression in the first months ( P  = .056). No advantages were found for indolent PPL who received immuno‐chemotherapy or more conservative approaches. Conclusion: Our studies confirm the epidemiological and favorable survival of patients with PPL, suggesting a very conservative approach, particularly in indolent subtypes.